2019
DOI: 10.1038/s41366-019-0474-1
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative liking and wanting for sweet beverages as predictors of body weight loss after Roux-en-Y gastric bypass and sleeve gastrectomy

Abstract: Background/objectives: Patients who receive Roux-en-Y gastric bypass (RYGB) lose more weight than those who receive vertical sleeve gastrectomy (VSG). RYGB and VSG alter hedonic responses to sweet flavor, but whether baseline differences in hedonic responses modulate weight loss after RYGB or VSG remains untested. Participants/methods: Male and female candidates (n=66) for RYGB or VSG were recruited and tested for their subjective liking and wanting ratings of sucrose solutions and flavored beverages sweetened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…These findings are in accordance with those reported by Nielsen et al where, despite the absence of a specific effect of GB or SG on food preferences measured directly in a buffet, patients that shifted food preferences were also those that lost more weight, reinforcing the possibility that variable modulation of the physiological mechanisms that influence food reward may underlie heterogeneity in response to surgery ( 41 ). Our results also expand on previous work showing an interaction between presurgical sucrose wanting ratings—but not aspartame wanting, sucrose liking, or aspartame liking—and bariatric surgery type (GB compared with SG) on predictions of weight loss ( 23 ). Another recent study has shown that higher presurgical liking ratings for sugar-sweetened milk predicted greater weight loss 6 months after GB ( 15 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings are in accordance with those reported by Nielsen et al where, despite the absence of a specific effect of GB or SG on food preferences measured directly in a buffet, patients that shifted food preferences were also those that lost more weight, reinforcing the possibility that variable modulation of the physiological mechanisms that influence food reward may underlie heterogeneity in response to surgery ( 41 ). Our results also expand on previous work showing an interaction between presurgical sucrose wanting ratings—but not aspartame wanting, sucrose liking, or aspartame liking—and bariatric surgery type (GB compared with SG) on predictions of weight loss ( 23 ). Another recent study has shown that higher presurgical liking ratings for sugar-sweetened milk predicted greater weight loss 6 months after GB ( 15 ).…”
Section: Discussionsupporting
confidence: 86%
“…It is also unknown whether presurgical ratings of palatable food can be used to predict weight loss after surgery. Wanting, but not liking, for sucrose solutions discriminated weight loss profiles differentially after GB and SG in one study ( 23 ). In another study, a GB-specific effect for liking, rather than wanting, scores of sucrose-sweetened milk, as well as reduced responses to sucrose-sweetened milk beverages in the ventral tegmental area, were predictive of increased weight loss ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Existing models of bariatric weight loss prediction tend to overestimate the outcome ( 56 ). However, a recent study published by Perez-Leighton et al showed the utility of preoperative classification of patients according to their sucrose-wanting rating in the selection of BS type ( 57 ). Patients with a high-wanting profile lost more weight after RYGB in comparison with sleeve gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Suppose it is possible to incorporate wider use of carefully constructed measures of both liking and wanting into human studies, it could provide greater insights into the nature of phenotypic differences in sweet liking. For example, recently, a study assessed sweet liking and wanting separately in obese patients prior to Roux-en-Y gastric bypass (RYGB) or vertical sleeve gastrectomy (VSG) surgery [164]. Their sweet-wanting, but not sweet-liking, rating predicted weight loss in their RYGB, but not VSG, patients.…”
Section: Why Might Evidence That Sweet-liking Drives Overconsumption ...mentioning
confidence: 99%